Taxidermy caribou family (Philadelphia Evening Bulletin, 1934)
"'Swe-e-et Ad-o-o-li-ine'--Peary's white caribou are not exactly famous for their singing, but it looks as if this bull caribou is trying to square himself with Ma Caribou and little Joe for maybe staying out one of those six-months Arctic nights. These big white animals are very rare, and live in temperatures 50 and 60 degrees below zero." With clipping